2020
DOI: 10.1039/d0nr05727d
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 nanosheets grown on hollow carbon spheres as a strong polysulfide anchor for high performance lithium sulfur batteries

Abstract: Lithium sulfur batteries are expected to be one of the most promising energy storage systems due to their high energy density, low cost and environmental friendliness. However, the shuttle effect...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…3,20 Through reducing the particle size of MoS 2 into the nanometer scale, the diffusion distance of Li + /Na + ions can be effectively shortened, thereby accelerating the reaction kinetics. Another strategy is to form MoS 2 /carbon-based nanocomposites with a special design to partly enhance the electrochemical properties of alkali metal ion batteries, such as MoS 2 /graphene networks, 21,22 CNTs@C@MoS 2 nanoarchitectures, 23 bowl-like C@MoS 2 nanocomposites, 24 hierarchical MoS 2 /N-doped carbon nanobelts, 25 MoS 2 @hollow carbon spheres, 26 etc. However, although this combination method can solve the problems of electrode conductivity and structural degradation, in most cases, the MoS 2 is usually loaded on the surface of the substrate, which is in direct contact with the electrolyte and suffers from drastic aggregation and unwanted side reactions during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…3,20 Through reducing the particle size of MoS 2 into the nanometer scale, the diffusion distance of Li + /Na + ions can be effectively shortened, thereby accelerating the reaction kinetics. Another strategy is to form MoS 2 /carbon-based nanocomposites with a special design to partly enhance the electrochemical properties of alkali metal ion batteries, such as MoS 2 /graphene networks, 21,22 CNTs@C@MoS 2 nanoarchitectures, 23 bowl-like C@MoS 2 nanocomposites, 24 hierarchical MoS 2 /N-doped carbon nanobelts, 25 MoS 2 @hollow carbon spheres, 26 etc. However, although this combination method can solve the problems of electrode conductivity and structural degradation, in most cases, the MoS 2 is usually loaded on the surface of the substrate, which is in direct contact with the electrolyte and suffers from drastic aggregation and unwanted side reactions during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition energy below 0.1 eV/atom shows a stable corresponding structure. In this study, we focus on AB 2 -type layered materials because they have been demonstrated as promising lithium–sulfur battery host materials due to their large surface area and shuttle-effect suppression. ,, To construct the ML training set, 65 compounds were selected from the 342 AB 2 -type structures for DFT optimization and adsorption energy calculation (Figure c). XGBoost was employed to rapidly classify the 342 compounds, and 98 potential materials were selected with adsorption greater than 1.0 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The two peaks ascribed to Mo 4+ 3d 3/2 and Mo 4+ 3d 5/2 in the Mo 3d spectrum shift toward lower binding energies after interacting with Li 2 S 6 (Figure 4c). The binding energy changes in the O 1s and Mo 3d spectra can be attributed to electron transfer among different species during the adsorption process, 52 thus confirming that MoS 2 /MoO 2 heterojunctions can provide strong adsorption toward LPSs. Simple blocking may be insufficient in the presence of high concentrations of LPSs.…”
Section: Resultsmentioning
confidence: 99%